Analisis pengetahuan pada siswa SMA di Balikpapan Selatan: mengenai mitigasi bencana tanah longsor - Muhammad Ryan Syarif Hidayatullah; Fajar Nur Rohman; Salsabila Aurellia Putri Perihanto; Adib Djaki Pratama; Andi Marini (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Landslides are the movement of soil structures and rock mixtures that move down lower areas around them. Indonesia is one of the countries with a high level of natural disasters, landslides. Balikpapan is one of the areas prone to natural disasters, especially landslides. This study aims to determine the extent of understanding of high school students in South Balikpapan regarding landslide disaster mitigation. The methodology of this study uses several methods, including document studies from relevant scientific journals as references and materials in formulating questions that will be entered into Google Form as a data collection tool. In this case, we chose high school students in South Balikpapan to be respondents regarding the knowledge of high school students in South Balikpapan regarding landslide disaster mitigation, considering that the Balikpapan area is a hilly area which is one of the factors causing landslide disasters. From the results of the research conducted, there are varying data regarding students' understanding of landslide disaster mitigation. The data obtained were 453 students from 4 schools in South Balikpapan. From the data it shows that there are 337 students who have received information or socialization about landslide prevention and 116 students have never received information or socialization about landslide prevention. The conclusion of the study shows that there are still some students who do not receive information or socialization about landslide disaster mitigation. This finding provides knowledge for educational institutions or related parties in efforts to mitigate landslide disasters.